1636 : mission to the Mughals - Flint, Eric; Barber, Griffin (Ring of fire (Riverdale, N.Y.), 2017)
"The United States of Europe, the new nation formed by an alliance between Swedish king Gustavus Adolphus and the West Virginians hurled back in time, need a reliable source of opiates for those wounded in action, as well as other goods not available in Europe. USE prime minister Mike Stearns sends a mission to the Mughal Empire of India with the aim of securing a trade deal with the emperor, Shah Jahan. Consisting of both up-timers and down-timers they arrive to find a grieving emperor obsessed with building the Taj Mahal, the emperor's sons plotting against each other and a war brewing with the newly risen Sikh faith. In the midst of all this they find an ally: brilliant Jahanara Begum, eldest daughter of Shah Jahan and a power in her own right. She wishes to learn more of these women who are free in a way she can scarcely comprehend"--